2003
DOI: 10.1001/archinte.163.10.1220
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial of Structured Treatment Interruptions in Human Immunodeficiency Virus Infection

Abstract: Results of this study do not favor the autovaccination hypothesis. Treatment interruptions did not provoke clinical complications, and there was little drug resistance. Comparative trials will have to show what benefit, if any, is associated with intermittent, as opposed to continuous treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
131
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 30 publications
5
131
2
Order By: Relevance
“…In brief, interruption of therapy recreates the same situation that occurs during an acute infection by HIV; that is, a biphasic fall in the number of CD4 lymphocytes, HIV RNA levels that peak and then fall spontaneously in most patients [14], and the achievement of a virological setpoint after about 4 months [10]. The factors predicting the loss of CD4 cells are the same as those for the natural infection and, for similar CD4 cell counts, the same clinical events already observed prior to ART recur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In brief, interruption of therapy recreates the same situation that occurs during an acute infection by HIV; that is, a biphasic fall in the number of CD4 lymphocytes, HIV RNA levels that peak and then fall spontaneously in most patients [14], and the achievement of a virological setpoint after about 4 months [10]. The factors predicting the loss of CD4 cells are the same as those for the natural infection and, for similar CD4 cell counts, the same clinical events already observed prior to ART recur.…”
Section: Discussionmentioning
confidence: 99%
“…There is, in fact, no doubt that the diversity of the results of studies on TI is related to the different study designs. A CD4 lymphocyte count of 350 cells/mL was considered an indication for interrupting therapy in the SMART [1] The efficacy and safety of the new therapeutic strategies must be evaluated in randomised studies, but, in order to plan such studies, it is important that the immunological, virological and clinical events related to the TI are fully understood so that appropriate patients are selected and the criteria for resuming therapy are correct.It has been demonstrated that, after TI, the viral load rebounds to pre-ART levels [8][9][10][11][12][13][14][15], and several studies on CD4-guided TI have evaluated the predictive factors for the duration of the first TI, with the nadir CD4 lymphocyte count emerging as the most constant and influential of these factors [8][9][10][16][17][18][19].In previous studies on the cohort of patients presented here, we noted that, during TI, the time taken to lose the CD4 cells recovered during ART was independent of the nadir CD4 count [19] and that the correlation between the duration of the first TI and the nadir CD4 count was a result of the fact that the resumption of ART started at CD4 cell counts different from the nadir counts. According to the criteria for resuming treatment that we adopted, patients with a CD4 nadir count o200 cells/mL had to restart treatment at a CD4 cell count above their nadir count and had a short TI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical trials found that the likelihood of STI to induce immunologic control of HIV replication was generally most favorable for patients who were started on HAART during acute infection, when the immune system was still relatively intact and when early treatment was able to lower the viral RNA set point after drug withdrawal (30,50). When treatment was started during chronic HIV infection, STI regimens were generally able to augment anti-HIV CD8 ϩ cell-mediated immune responses (to approximately pretreatment levels) but were less effective in restoring and maintaining HIV-specific CD4 ϩ cellular immune responses, and treatment interruptions generally led to a viral rebound to near pretreatment levels (17,20,44,45,(47)(48)(49)51).…”
mentioning
confidence: 99%
“…We were not able to define any viral or immunologic parameters early in infection that were predictive of the final outcome. For HIVinfected adults receiving STI, the viral set point after treatment interruption was significantly associated with the pretreatment plasma viremia and CD4 ϩ cell counts (20,45,49,73,77), but these people were started on treatment during chronic infection; in other words, the pretreatment virus load set point was already determined by the strength of antiviral immune responses at that time. In our infant macaque study, because treatment was started 5 days after virus inoculation, antiviral immune responses were still in very early stages, and viral RNA levels at the start of treatment or during the initial treatment course were not predictive of the subsequent virologic outcome.…”
mentioning
confidence: 99%